2020
DOI: 10.21203/rs.3.rs-35911/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coronavirus disease 2019 outbreak: does confinement have any impact on weight variation and weight change perception?

Abstract: Background: In the time of confinement, a reduction of physical activities, unhealthy diet, sedentary behavior, and an increase in sitting time will contribute to weight change. During these stressful times, individuals might have a greater concern about their body image and weight. Therefore, the first objective of the current study is to evaluate the impact of confinement during the COVID-19 outbreak on weight variation. The second objective is to evaluate factors associated with weight perception among a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…This study has also some strengths. One above all is represented by the fact that the survey was conducted after two months of lockdown, and not just a few weeks after closing or during isolation, as it was previously shown/demonstrated that a prolonged confinement is considerably associated with a greater perception of weight change [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has also some strengths. One above all is represented by the fact that the survey was conducted after two months of lockdown, and not just a few weeks after closing or during isolation, as it was previously shown/demonstrated that a prolonged confinement is considerably associated with a greater perception of weight change [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study has also some strengths. One above all is represented by the fact that the survey was conducted after two months of lockdown, and not just a few weeks after closing or during isolation, as it was previously shown/demonstrated that a prolonged confinement is considerably associated with a greater perception of weight change [61]. This is a snapshot illustrating a specific moment of the first national lockdown experienced in Italy, without being able to properly catch the changes over time in the variables considered with respect to the pandemic continue, even though it could be useful for future comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Lebanese ones, had demonstrated weight gain during the COVID-19 home con nement [2,25,[46][47][48], likely due to boredom, anxiety, and stress reactions to COVID-19 leading to changes in eating habits, such as increased consumption of highly energetic foods (rich in sugar and fat) [49].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were conducted to assess the effects of the COVID-19 pandemic on Lebanese adults, covering mental health, domestic violence, weight change, stress, and anxiety [24][25][26][27]. Their ndings revealed that the fear of COVID-19 was associated with a negative weight perception [25] and higher stress and anxiety, particularly in women [26]. Furthermore, extended con nement was associated with a higher weight change perception [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation